Cancer du sein pendant la grossesse : enjeux cliniques et avancées thérapeutiques au sein du service d'oncologie médical de Bordj Bou Arreridj et au service d'oncologie médical anti cancer el BEZ à Sétif - KHARCHI , Amar; HIMA , Mayar; HAMMOUCHE , Lina; HAMIDECHE , Khalil; GHENNAM , Ahlem (Encadrant) (Université Sétif1 Ferhat Abbas. Faculté de Médecine., 2024)
Although breast cancer during pregnancy is relatively rare in Algeria from a clinical standpoint, it is not exceptional, with an incidence of about 1 in 1000 pregnancies. Understanding the recommended management for a patient with cancer during pregnancy can provide insights into the challenges and obstacles encountered throughout this medical journey. A clinical analysis of records conducted within the medical oncology department of Bordj Bou Arreridj and the medical oncology department of Sétif, covering 7 cases of women suffering from breast cancer during and after pregnancy, aimed to evaluate the complex management of this pathology when a second life is at stake. The study reveals the relatively young average age of the patients, with an average of 37 years, and the majority of cases diagnosed during pregnancy (5 out of 7). Histological analysis shows a predominance of SBR grade III, although one case of SBR grade II suggests diversity in histological presentations. Assessments of hormone receptors and HER2 status indicate significant variability in these biological markers. Therapeutic management, in accordance with international recommendations, generally includes a combination of treatments such as surgery and chemotherapy (mainly in the second and third trimesters), while hormone therapy, radiotherapy, and targeted therapies are postponed to the postpartum period. Significant advances have been made in managing breast cancer during pregnancy in recent years, despite the challenges encountered at different stages of the management process. It is crucial to raise awareness among patients about the risks associated with a potential pregnancy during their treatment.
لى الرغم من أن سرطان الثدي أثناء الحمل نادر نسب ًيا في الجزائر من الناحية السريرية، إلا أنه ليس استثنائيًا، حيث تبلغ نسبة حدوثه حوالي 1لكل 1000حالة حمل. فهم الإجراءات الموصى بها للمريضة المصابة بالسرطان أثناء الحمل يمكن أن يزودنا برؤى حول التحديات والعقبات التي يتم مواجهتها على طول هذا المسار الطبي. تحليل سريري للسجلات أجري في قسم الأورام الطبية في برج بوعريريج وقسم الأورام الطبية في سطيف، شمل 7حالات لنساء يعانين من سرطان الثدي أثناء وبعد الحمل، بهدف تقييم الإدارة المعقدة لهذه الحالة المرضية عندما تكون حياة ثانية على المحك. تكشف الدراسة عن متوسط العمر النسبي الشاب للمريضات، بمتوسط 37عا ًما، ومعظم الحالات التي تم تشخيصها أثناء الحمل ( 5من أصل .)7التحليل النسيجي يُظهر غلبة الدرجة ،SBR IIIعلى الرغم من أن حالة واحدة من الدرجة SBR IIتشير إلى تنوع في العروض النسيجية. تقييمات مستقبلات الهرمونات وحالة HER2تشير إلى تباين كبير في هذه المؤشرات البيولوجية. الإدارة العلاجية، وفقًا للتوصيات الدولية، تتضمن عمو ًما مجموعة من العلاجات مثل الجراحة والعلاج الكيميائي (بشكل رئيسي في الثلث الثاني والثالث من الحمل،) بينما يتم تأجيل العلاج الهرموني والعلاج الإشعاعي والعلاجات المستهدفة إلى فترة ما بعد الولادة. حققت إدارة سرطان الثدي أثناء الحمل تقد ًما كبي ًرا في السنوات الأخيرة، رغم التحديات التي يتم مواجهتها في مراحل مختلفة من عملية الإدارة. من الضروري زيادة الوعي بين المريضات حول المخاطر المرتبطة بحمل محتمل أثناء العلاج
Keywords: cancer du sein; grossesse; complications; malformations